THE PROSECUTOR'S AUTHORITY IN CRIMINAL LAW ENFORCEMENT WITH A RESTORATIVE JUSTICE APPROACH - Alfi Nur Fata (UNISSULA Semarang, 2021)
This study aims to identify and describe the authority of the Prosecutor's Office in enforcing criminal law with a restorative justice approach. This study uses a normative juridical approach with descriptive analysis. The data used is secondary data obtained through literature study, which is then analyzed qualitatively. The results of this study are the authority of the Prosecutor's Office in enforcing criminal law with a restorative justice approach based on the principle of opportunity, which is regulated in Law Number 16 of 2004 Article 35 letter c of Law Number 16 of 2004, Elucidation of Article 77 of the Criminal Procedure Code, and Law No. Number 11 of 2012. The principle of opportunity needs to be given to all prosecutors, in order to be able to resolve criminal cases that according to the community do not need to be resolved to court. With the authority of opportunity, each Prosecutor can explore and discover the values of justice that grow and develop in social life. Currently, the application of restorative justice by the Prosecutor's Office has been regulated in the Regulation of the Prosecutor's Office of the Republic of Indonesia Number 15 of 2020, in which the application of restorative justice is carried out by closing cases in the public interest through cessation of prosecution. Keywords: Restorative Justice, Prosecutor's Office, Authority, Law Enforcement, Criminal